FILOSOFINIS ETIUDAS APIE MOTERS SPRENDIMO GELMĘ. - Pučiliauskaitė, Saulenė (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2010)
In this article we present an earnest effort to think about the nature of a woman's decision. Thus, we ask our readers to think about one of the most important decisions of a woman's life in philosophical terms. To achieve this aim, we investigate the relations between the concept of choice and the concept of decision. Our method of thinking is the analysis of the novel by Virgina Woolf 'Mrs. Dalloway', in which we see as an example of the problem (even 'heart' and 'sincerity' find their places in it). We also take a brief glance into 'Orlando' and a few sentences of Kant's 'Critique of Practical Reason' to explore the relations between the concepts of 'man' and 'personality' and discover that the concept of 'man' is much more relevant in this case. We explore the motives of woman's saying 'Yes' and saying 'No' and find out, that saying 'No' is much clearer than saying 'Yes'. The ground of saying 'Yes' remains obscure. All our effort is directed to illlustrate speaking (writing, thinking) in a 'woman's voice'(Derrida).